2007
DOI: 10.1109/robot.2007.363112
|View full text |Cite
|
Sign up to set email alerts
|

STRIDE: A Highly Maneuverable and Non-Tethered Water Strider Robot

Abstract: Recently, a few water strider robots that mimic the static and dynamic key characteristics of the insect water striders have been reported in the literature. These robots either lacked mobility or was tethered to an external source of power. Using the recent findings on the supporting legs of these robots creating repulsive surface tension based lift forces, a heavier yet highly maneuverable and non-tethered water strider robot, called STRIDE, is proposed in this paper. STRIDE uses two miniature DC motors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…1, the ten supporting legs are fixed on the body horizontally and in line with an assigned center distance of about 10 mm on average. This supporting mechanism has been used for several water strider robots to provide a large surface tension force upward in a confined space [5], [15], [17]. Previous studies showed that decreasing the leg center distance will decrease the maximum lift force [13].…”
Section: A Supporting Mechanismmentioning
confidence: 99%
“…1, the ten supporting legs are fixed on the body horizontally and in line with an assigned center distance of about 10 mm on average. This supporting mechanism has been used for several water strider robots to provide a large surface tension force upward in a confined space [5], [15], [17]. Previous studies showed that decreasing the leg center distance will decrease the maximum lift force [13].…”
Section: A Supporting Mechanismmentioning
confidence: 99%
“…In the case of water strider robots, when we consider that the value of surface tension force is proportional to the length of the three phase contact line, increasing the overall length of the supporting legs is an effective approach for improving load capacity. Given limited overall size, a multi-leg mechanism composed of several cylinders fixed horizontally and in line with an assigned center distance (Figure 4(a)), is widely used in the design of water strider robots, including such as STIDER, 6 Water dancer II, 10 and Screw-type water strider robot 11 ). Sitti et al 5 previously claimed the distance between the neighboring legs of water strider robots should be large enough to maximize the lift force, which is inconsistent with the above conclusion that cylinders with a larger center distance will have a smaller load capacity.…”
Section: A Cylinder Center Distancementioning
confidence: 99%
“…The robots, whose legs consist of spindly cylinders decorated with hydrophobic materials, are based on the fundamental principles of the water strider's ability to float and move on the water surface. 1,[5][6][7][8][9][10][11] It is of interest to consider how great a load these cylindrical legs can support on a water surface.…”
Section: Introductionmentioning
confidence: 99%
“…This robot has concentric circular footpads that are designed, analysed and manufactured using laser-cutting to generate more lift force per unit area and greater stability when compared to STRIDE [19]. Moreover, the drag force model of the supporting structure and the propulsion mechanism are investigated and explained in detail.…”
Section: Introductionmentioning
confidence: 99%